Reduced age at first calving: effects on lifetime production, longevity, and profitability - M. J. Meyer; R.W. Everett; Amburgh M.E. Van (Kansas Agricultural Experiment Station Research Reports, 2004)
The primary advantages of reducing age at first calving (AFC) include reducing rearing costs as well as reducing time in which the heifer is only a capital drain on farm resources. The primary disadvantage of reducing AFC is that it is frequently associated with a reduction in first-lactation milk yield. Despite this reduction in first-lactation milk yield, production per year of herd life is typically increased by reduced AFC. Furthermore, although the first lactation yield may be influenced by AFC, future lactations are decidedly not. In addition, stayability and health of cows are not influenced by reduced AFC as long as heifers freshen at an adequate weight. Most analyses indicate that the financial advantage afforded from heifers that freshen at a low AFC seems to at the least offset any milk lost during the first lactation. Furthermore, when the time value of money is considered in this analysis, a reduced AFC (~22 months) seems likely to represent a more fiscally sound management decision. When applying these ideas on the farm, a properly managed feeding and breeding program should permit a firstlactation cow to weigh ~1,210 lb after freshening at 22 months of age. The National Research Council recommends a postpartum weight equal to 82% of her mature body weight. This can be achieved with a maximal prepubertal average daily gain (ADG) of 2 lb/day when a traditional preweaning program is employed or 1.8 lb/day when an intensified preweaning program is employed. Because of the well defined link between inadequate body weight at calving and increased mortality and morbidity in first-lactation cows, achieving this target post-calving body weight is of critical importance.; Dairy Day, 2004, Kansas State University, Manhattan, KS, 2004;
Keywords: Dairy Day; 2004; Kansas Agricultural Experiment Station contribution; no. 05-112-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 941; Dairy; Heifers; Growth; Age at first calving